Cover Picture: Study on Burning and Thermal Decomposition Properties of HTPB Propellant Containing Synthesized Micro‐nano Ferric Perfluorooctanoate (Prop., Explos., Pyrotech. 3/2019). Issue 3 (5th March 2019) - Zhen, Fei; Zhou, Xu‐Yuan; Wang, Li‐Qiong; Yang, Rong‐Jie; Huang, Feng‐Lei
Abstract : The cover picture shows a novel micro‐nano ferric perfluoroocate [Fe(PFO)3 ] as an unusual catalyst multifaceted effects on AP/Al/HTPB composite solid propellant. Our study shows that Fe(PFO)3 could improve the burning rate of the propellant as well as suppress the combustion agglomeration process. Fe(PFO)3 could also decrease the thermal decomposition temperature of Al/AP/HTPB composite solid propellant and the heat release. Impressively, The decomposition products of Fe(PFO)3 were proved to trigger the thermite reaction with Al at 635 °C leading to large heat release and formation of α‐Al2 O3 . Details are discussed in the article by Fei Zhen et al. on page 362 ff.